Teachers’ self-reported instructional practices for reading comprehension instruction to non-readers - Mpofu, Nhlanhla; Mavambe, Tsitsi (ELT Worldwide: Journal of English Language Teaching, 2023)
This study focuses on the instructional strategies employed by experienced teachers to teach reading comprehension to non-readers in the Namibian upper primary phase within mainstream classrooms. Existing literature suggests that the support provided by experienced teachers is critical for non-readers. However, little is known about the specific strategies used by primary school ESL (English as a Second Language) teachers in Namibia for this purpose. To address this gap, the study utilized a qualitative approach with an exploratory case study design. Data was gathered through class observations and two stimulated recall interviews conducted before and after the observations. Five Grade 5 teachers in the Oshana region of Namibia were purposefully selected as participants. The findings reveal that the teachers employed various strategies to enhance reading comprehension among non-readers. Pre-reading activities involved activating non-readers’ linguistic schema using manipulatives, dictionaries, and glossaries to define new words. Linguistic resources such as flashcards, wall posters, real objects, and pictures were used to expand non-readers’ vocabulary knowledge. Instructional reinforcement strategies, like motivation, activation of prior knowledge through oral discussions, games related to the text, and discussions of reading comprehension rules, were also utilized to support non-readers’ comprehension. The findings hold value for Grade 5 ESL teachers, providing them with effective teaching strategies and opportunities for self-reflection when teaching reading comprehension to non-readers. Additionally, ESL subject advisors can benefit from understanding the needs of primary school non-readers in the Ompundja circuit, Oshana region, to offer appropriate support to upper primary phase ESL teachers in mainstream classes.